From Guidelines to Clinical Practice: Expert Perspectives on Long‐Term Management of Obesity - Hong Chen; Ling Li; Junqing Zhang; Shaihong Zhu; Marc‐André Cornier; Jonathan Q Purnell (Obesity, 2026)
ABSTRACT An international panel of experts from the U.S. and China convened to discuss the 2026 TOS–OMA–OAC Expert Guidance Statement on the Pharmacological Management of Obesity, focusing on emerging evidence, regional considerations, and challenges in translating recommendations into long‐term care. Panelists reached a consensus that obesity should be recognized as a chronic and progressive disease, for which pharmacotherapy is lifelong once initiated, as discontinuation consistently leads to weight regain and loss of metabolic benefit. The discussion highlighted a shift toward treating obesity itself as an upstream intervention capable of modifying multiple obesity‐related complications, with greater weight loss generally conferring greater clinical benefit. Visceral adipose tissue emerged as a particularly relevant therapeutic target, especially in Asian populations, where substantial metabolic risk may be present at lower BMI levels. Panelists noted heterogeneity in treatment response and that eventual weight‐loss plateaus should be anticipated as evidence of maximal effectiveness rather than medication failure. The panel endorsed an individualized, stepwise approach integrating pharmacotherapy and metabolic surgery as complementary strategies. Finally, the panel emphasized that translating therapeutic advances into real‐world benefit will require addressing practical barriers related to policy, access, affordability, and stigma to ensure effective care reaches those who need it most.